2022
DOI: 10.52965/001c.34222
|View full text |Cite
|
Sign up to set email alerts
|

pitolisant, a novel histamine-3 receptor competitive antagonist, and inverse agonist, in the treatment of excessive daytime sleepiness in adult patients with narcolepsy

Abstract: Narcolepsy is a debilitating sleep disorder that presents with excessive daytime sleepiness (EDS) and cataplexy, which is a sudden paralysis of muscle tone triggered by strong emotions such as laughing. It is also associated with many other disorders, including psychiatric disorders, neurologic illnesses, and medication side effects. Common causes of delayed and incorrect diagnoses of these conditions include lack of physician familiarity with narcolepsy symptoms and comorbidities which mask narcolepsy signs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Asimismo, modula la actividad de otros neurotransmisores, aumentando los niveles de acetilcolina, noradrenalina y dopamina, sin actuar sobre las neuronas dopaminérgicas del núcleo accumbens , por lo que no presenta riesgo de adicción. De esta manera, al potenciar la actividad histaminérgica, mejora el nivel de alerta, la duración de la vigilia y los episodios de cataplejía [ 7 , 8 ].…”
Section: Discussionunclassified

Narcolepsia multirresistente

González García,
Morán Sánchez,
Sánchez Serrano
et al. 2023
RevNeurol
“…Asimismo, modula la actividad de otros neurotransmisores, aumentando los niveles de acetilcolina, noradrenalina y dopamina, sin actuar sobre las neuronas dopaminérgicas del núcleo accumbens , por lo que no presenta riesgo de adicción. De esta manera, al potenciar la actividad histaminérgica, mejora el nivel de alerta, la duración de la vigilia y los episodios de cataplejía [ 7 , 8 ].…”
Section: Discussionunclassified

Narcolepsia multirresistente

González García,
Morán Sánchez,
Sánchez Serrano
et al. 2023
RevNeurol
“…Interestingly, histamine also modulates the wake-sleep cycle in higher organisms. For instance, pitolisant (H3R receptor antagonist/inverse agonist) is a narcolepsy treatment option [82,83] and modafinil (a drug increasing histamine release in the neocortex and hypothalamus [84,85]) is a wake-promoting agent to treat hypersomnolence [86,87]. These results certainly encourage further research on the role of histamine in the sleep-wake cycle and circadian rhythm regulation.…”
Section: Wake-sleep Cyclementioning
confidence: 98%
“…Different from traditional stimulants, pitolisant works by enhancing the release of histamine, promoting wakefulness and reducing excessive sleepiness 14 . The robust efficacy of pitolisant for the reduction in both EDS and cataplexy has been demonstrated 15–18 . In addition, pitolisant has been found to be well‐tolerated and has a low risk of abuse.…”
Section: Introductionmentioning
confidence: 99%
“… 14 The robust efficacy of pitolisant for the reduction in both EDS and cataplexy has been demonstrated. 15 , 16 , 17 , 18 In addition, pitolisant has been found to be well‐tolerated and has a low risk of abuse. Recent real‐world studies have suggested that pitolisant treatment is effective in children with narcolepsy and also is well tolerated.…”
Section: Introductionmentioning
confidence: 99%